L’intensification des pratiques agricoles et la mobilisation des ressources naturelles dans La Pampa du Sud du Brésil - Jeannine Corbonnois (Éditions en environnement VertigO, 2014)
Southern Brazil, which has a good natural potential due to its sub-tropical climate and its favorable topography, is mainly dedicated to breeding and cultivating soybean, rice and corn. Like others in Brazil, this region is involved in the production of agricultural products for domestic and international markets. It is thus subject to the intensification of practices whose impacts on the environment are well known. The study investigates the watershed of Ibicuí (46.800 km²), located in the southwest of the state of Rio Grande do Sul. Thanks to interpretation of MODIS images, we have identified land uses and its transformations during the first decade of the twenty-first century. The cards we have been able to achieve are analyzed and confronted with surveys of agriculture stakeholders (local agriculture organizations, farmers…), carried out between 2007 and 2010. The analysis of three specific areas allows determining agricultures’s impacts and pressure on the environment : the sector of Rosario do Sul is undergoing a decline of livestock and a rise of eucalyptus plantations, while Alegrete area is dedicated to rice crops and São Francisco de Assis area is undergoing the erosion of its sandy soils and the return of the meadow. The paper examines how the environment is integrated through water uses management, through the development of innovating cultural practices like direct seeded soil systems and through environmental protection such as the laws of 2002 and 2006 on Permanent Protection Areas (APP).